A catalogue of the types of rove beetles (Coleoptera: Staphylinidae) deposited in the collection of Johan Heinrich Hochhuth in the National Museum of Natural History of the National Academy of Sciences of Ukraine - Glotov, Serhii V.; Martynov, Alexander V.; Shavrin, Alexey V. (Zootaxa, 2022)
Type specimens of Staphylinidae (Coleoptera) from the collection of J.H. Hochhuth (1810–1872) deposited in National Museum of Natural History of the National Academy of Sciences of Ukraine (Kyiv) are currently being catalogued and illustrated. This catalogue presents information about 103 type specimens (14 holotypes, 80 lecto- and paratypes, and nine syntypes) belonging to 67 nominal species. Several lectotypes are designated: Conurus erythrocephalus Hochhuth, 1849, Aleochara solida Hochhuth, 1849, Trogophloeus kiesenwetterii Hochhuth, 1851, Ocypus pullus Hochhuth, 1849, Philonthus armeniacus Hochhuth, 1851, P. interpunctatus Hochhuth, 1860, and P. subopacus Hochhuth, 1851.